Cytokines and local chronic inflammation in the formation of infertility in fertile age women - O. O. Obukhova; A. N. Trunov; O. M. Gorbenko; A. P. Shvayuk (Сибирский научный медицинский журнал, 2020)
The purpose of the study was to examine the characteristics of the content of cytokines in the peritoneal fluid in women of reproductive age with infertility against the background of chronic inflammatory diseases of the pelvic organs in the stage of clinical remission.Material and methods. A study was conducted of 50 patients aged 23-36 years with a verified diagnosis of infertility of tubal peritoneal genesis against a background of chronic inflammatory diseases of the reproductive sphere in the stage of clinical remission. As a control group, 15 practically healthy women aged 25-37 years were examined. Concentration of cytokines TNF-a, IL-4, IL-6, IL-10, IFN-y, MCP-1 in the peritoneal fluid was measured by enzyme-linked immunosorbent assay.Results and discussion. In the main group of patients with tubal-peritoneal infertility, the activity of local inflammatory reactions is tested in the period of clinical remission of a chronic inflammatory process. This is confirmed by a significantly higher level of TNF-a, IL-4, IL-6, IFN-y, MCP-1 in the peritoneal fluid compared to the control group. The studied biologically active substances play a significant role in the development of the immune response, as well as fibroplastic processes. The results can be regarded as the latent development of the immune response in reactions to constant antigenic stimulation from the focus of chronic inflammation, which is a significant factor in the development of adhesions in the formation of infertility, and requires the inclusion of immunotropic therapy methods in treatment.